Does it Pay to Watch Central Bankers' Lips? The Information Content of ECB Wording - Friedrich Heinemann; Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
In this analysis, the informational content of central bank rhetoric is assessed based on the experience with the ECB since 1999. Among the ECB?s communication channels we focus on the monthly press conferences. Based on a counting of certain signal words we construct a wording indicator reflecting the ?hawkishness? of monetary rhetorics. For the construction, we develop an objective algorithm representing a learning process of ECB observers. We then integrate this indicator into a standard Taylor type ordered probit model for the explanation of the interest rate. We show that the wording indicator can improve the model?s fit when added to the standard explanatory variables. However, a model based solely on this indicator performs worse than the baseline. The results are confirmed by out of sample analysis where the determination of the wording indicators? weights is based on the early ECB period which, subsequently, is excluded from the tests. Our conclusion is that linguistic analysis can improve but not substitute more rigorous forecasting techniques based on hard economic data.
Keywords: E43; E52; 330; Taylor rule; wording; central bank communication; Zentralbank; Europäische Wirtschafts- und Währungsunion; Staatliche Information; Informationswert; Taylor-Regel; Schätzung; EU-Staaten